Energy transmission in optical device makes for association of nonlinear directional coupler cascading - Nascimento, José Cláudio do (2014)
NASCIMENTO, J. C. Energy transmission in optical device makes for association of nonlinear directional coupler cascading. 2014. Artigo (2014 International Telecommunications Symposium), São Paulo, 2014.